2019
DOI: 10.1177/1753466619890538
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and pulmonary disease

Abstract: Autophagy is a process of cell self-renewal that is dependent on the degradation of the cytoplasmic proteins or organelles of lysosomes. Many diseases, such as metabolic diseases, cancer, neurodegenerative diseases, and lung diseases, have been confirmed to be associated with elevated or impaired levels of autophagy. At present, studies have found that autophagy participates in the regulation of chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis, pulmonary hypertension, acute lung inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 93 publications
(98 reference statements)
0
41
0
Order By: Relevance
“…A growing body of evidence supports an important role of autophagy in idiopathic pulmonary fibrosis ( ) [ [290] , [291] , [292] ] ( Fig. 4 ).…”
Section: Autophagy and Ros In Pulmonary Diseasesmentioning
confidence: 99%
“…A growing body of evidence supports an important role of autophagy in idiopathic pulmonary fibrosis ( ) [ [290] , [291] , [292] ] ( Fig. 4 ).…”
Section: Autophagy and Ros In Pulmonary Diseasesmentioning
confidence: 99%
“…MSCs might alleviate LPS-ALI via downregulation of miR-142a-5p that permits pulmonary epithelial cells (PECs) to proceed with Beclin 1-mediated cell autophagy [ 127 ]. In lung disease, the bacterial studies demonstrated that the penetration of Acinetobacter baumannii activated the ubiquitin-mediated autophagic response that depends on the septins SEPT2 and SEPT9 and it is due to the Beclin 1-dependent AMPK/ERK/mTOR pathway [ 128 ].…”
Section: Lung Injury: Clinical Implicationsmentioning
confidence: 99%
“…For example, Xue et al (17) demonstrated that apoptosis stimulating protein of p53 promotes tumor growth by increasing autophagic flux in human non-small cell lung cancer, whereas HECT domain and ankyrin repeat containing E3 ubiquitin protein ligase 1 (HACE1) acts as a tumor suppressor by ubiquitinating optineurin (OPTN) and activating selective autophagy (18). Autophagy is also involved in lung cancer therapy, chemotherapy induces tumor cell autophagy, and inhibiting autophagy enhances the sensitivity of lung cancer cells to chemotherapy (19).…”
Section: Introductionmentioning
confidence: 99%